2010
DOI: 10.1104/pp.110.153759
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Sulfur Deficiency on the Expression of Specific Sulfate Transporters and the Distribution of Sulfur, Selenium, and Molybdenum in Wheat

Abstract: Interactions between sulfur (S) nutritional status and sulfate transporter expression in field-grown wheat (Triticum aestivum) were investigated using Broadbalk +S and 2S treatments (S fertilizer withheld) at Rothamsted, United Kingdom. In 2008, S, sulfate, selenium (Se), and molybdenum (Mo) concentrations and sulfate transporter gene expression were analyzed throughout development. Total S concentrations were lower in all tissues of 2S plants, principally as a result of decreased sulfate pools. S, Se, and Mo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
102
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 154 publications
(111 citation statements)
references
References 42 publications
7
102
1
1
Order By: Relevance
“…Selenate supply had little effect on transcript abundance, and S starvation only resulted in a slight increase in the expression of group 1 and group 4 transporters in root tissues. This is in contrast to observations with other species, where the expression of many sulfate transporters has been shown to be highly induced by sulfate starvation (Smith et al, 1995(Smith et al, , 1997Takahashi et al, 2000;Shibagaki et al, 2002;Yoshimoto et al, 2002Yoshimoto et al, , 2003Howarth et al, 2003;Buchner et al, 2004aBuchner et al, , 2004bHopkins et al, 2004Hopkins et al, , 2005Koralewska et al, 2008Koralewska et al, , 2009Rouached et al, 2008;Shinmachi et al, 2010). The expression of one group 1 isoform, Sultr1;1, and one group 2 isoform, Sultr2;1, has also been shown to be induced by increased Se supply (Takahashi et al, 2000).…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Selenate supply had little effect on transcript abundance, and S starvation only resulted in a slight increase in the expression of group 1 and group 4 transporters in root tissues. This is in contrast to observations with other species, where the expression of many sulfate transporters has been shown to be highly induced by sulfate starvation (Smith et al, 1995(Smith et al, , 1997Takahashi et al, 2000;Shibagaki et al, 2002;Yoshimoto et al, 2002Yoshimoto et al, , 2003Howarth et al, 2003;Buchner et al, 2004aBuchner et al, , 2004bHopkins et al, 2004Hopkins et al, , 2005Koralewska et al, 2008Koralewska et al, , 2009Rouached et al, 2008;Shinmachi et al, 2010). The expression of one group 1 isoform, Sultr1;1, and one group 2 isoform, Sultr2;1, has also been shown to be induced by increased Se supply (Takahashi et al, 2000).…”
Section: Discussioncontrasting
confidence: 54%
“…Several studies have shown that a decrease in root sulfate availability results in a severalfold enhanced expression of sulfate transporter genes, which enhances the capacity for sulfate uptake and consequently enhances the uptake of Se (Hawkesford, 2000;Hawkesford et al, 2003;Shinmachi et al, 2010).…”
mentioning
confidence: 99%
“…Activating sulfate transporter is conducive to promoting Se uptake and translocation from roots to shoots in plants [51][52][53][54]. In this study, the data of RNA-Seq revealed that the release of VOCs released by BF06 induced the expression of sulfate transporter genes including SULRT1;1, SULRT1;2, SULTR2;1, SULTR2;2 and SULTR3;5, indicating that BF06 VOCs was likely involved in the regulation of Se uptake in Arabidopsis.…”
Section: Effects Of Bf06 Vocs On Se Accumulation In Plantsmentioning
confidence: 56%
“…In addition, the transcription of several sulfate transporter genes was significantly increased in the VOCs-exposed plants compared with the controls (Table S4). These sulfate transporter genes have been demonstrated to play essential roles in Se assimilation in Arabidopsis plants [51][52][53][54]. Thus, the VOCs-induced expression of sulfate transporter genes might participate in the regulation of Se accumulation in plants.…”
Section: Transcriptomic Analysis Of Bf06 Vocs-regulated Gene Profilesmentioning
confidence: 99%
“…After absorption, Mo served as a substrate of the reaction catalyzed by ATPs, but there was no molybdenum-containing product from this reaction due to adenosine 5'-phosphomolybdate was either not formed or not stable (Reuveny, 1977). It has been speculated that Mo could compete with sulfate ion for sulfate transporter and ATPs enzyme resulting in a lower sulfate metabolism and wasteful use of ATP (Hale et al, 2001;Shinmachi et al, 2010). MOT1 was up-regulated in B. juncea plants supplied with Mo, and the increase of Mo transporter accompanied with an accumulation of Mo in both roots and leaves (Schiavon et al, 2012).…”
Section: Discussionmentioning
confidence: 99%